(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study explores the work-life balance and role efficacy among nurses in selected hospitals of Uttarakhand. The findings indicate that most nurses are generally satisfied with their jobs, manage their workloads effectively, and experience a healthy work-life balance. Key factors enhancing their role efficacy include a supportive work environment, effective communication with management, access to necessary resources, job satisfaction, personal accomplishment, adequate training, and strong leadership. Recommendations include revisiting scheduling practices to introduce flexible work arrangements, specialized training programs to enhance skills, wellness programs focusing on mental health, and fostering a culture of respect and collaboration. Establishing effective communication channels and recognition programs is crucial for addressing concerns and enhancing role efficacy.